2011
DOI: 10.1088/0004-637x/736/1/40
|View full text |Cite
|
Sign up to set email alerts
|

Components of the Extragalactic Gamma-Ray Background

Abstract: We present new theoretical estimates of the relative contributions of unresolved blazars and star-forming galaxies to the extragalactic γ -ray background (EGB) and discuss constraints on the contributions from alternative mechanisms such as dark matter annihilation and truly diffuse γ -ray production. We find that the Fermi source count data do not rule out a scenario in which the EGB is dominated by emission from unresolved blazars, though unresolved star-forming galaxies may also contribute significantly to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
129
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(135 citation statements)
references
References 117 publications
(326 reference statements)
6
129
0
Order By: Relevance
“…Some authors have suggested that blazars could be the primary source of the EGB (e.g., Stecker & Venters 2011;Abazajian et al 2010), and the results of BP1 did not rule this out, while the results presented in Ajello et al (2012), Abdo et al (2010c), and Malyshev & Hogg (2011) favor blazars being one of several important classes of sources. Other possible source populations for the EGB include starforming galaxies, which have been proposed as a possible significant contributor to the EGB by, e.g., Stecker & Venters (2011), Fields et al (2010, and Lacki et al (2011), although this is countered by Makiya et al (2011), radio galaxies (e.g., Inoue 2011), and non-blazar AGNs (e.g., Inoue & Totani 2009, 2011.…”
Section: And One Is Left Withmentioning
confidence: 96%
See 1 more Smart Citation
“…Some authors have suggested that blazars could be the primary source of the EGB (e.g., Stecker & Venters 2011;Abazajian et al 2010), and the results of BP1 did not rule this out, while the results presented in Ajello et al (2012), Abdo et al (2010c), and Malyshev & Hogg (2011) favor blazars being one of several important classes of sources. Other possible source populations for the EGB include starforming galaxies, which have been proposed as a possible significant contributor to the EGB by, e.g., Stecker & Venters (2011), Fields et al (2010, and Lacki et al (2011), although this is countered by Makiya et al (2011), radio galaxies (e.g., Inoue 2011), and non-blazar AGNs (e.g., Inoue & Totani 2009, 2011.…”
Section: And One Is Left Withmentioning
confidence: 96%
“…Other possible source populations for the EGB include starforming galaxies, which have been proposed as a possible significant contributor to the EGB by, e.g., Stecker & Venters (2011), Fields et al (2010, and Lacki et al (2011), although this is countered by Makiya et al (2011), radio galaxies (e.g., Inoue 2011), and non-blazar AGNs (e.g., Inoue & Totani 2009, 2011.…”
Section: And One Is Left Withmentioning
confidence: 99%
“…There are several studies that derive the contribution to the EGB from star-forming galaxies (e.g. Fields et al 2010;Stecker & Venters 2011;Makiya et al 2011;Ackermann et al 2012;Chakraborty & Fields 2013;Lacki et al 2014;Tamborra et al 2014). The studies that analyze quiescent and starburst galaxies separately find that the starburst contribution is always comparatively minor and the total (quiescent plus starburst) γ-ray emission is between 10%-50% of the EGB intensity.…”
Section: Introductionmentioning
confidence: 99%
“…While it is tempting to invoke dark matter annihilations for the explanation of the extragalactic gamma-ray background, the background might also be due to a variety of astrophysical classes of sources. Among these, flat spectrum radio quasars [38] are the most studied, but there are also significant contributions from star-forming galaxies, radio galaxies and Bl Lacertae objects. In the same figure, we plot the spectrum of star-forming galaxies for the case when the spectrum is determined from the IR luminosity function model (dashed line), and the integrated flux of flat spectrum radio quasars (dotted line) [38].…”
Section: F Dark Matter Spike Mass Functionmentioning
confidence: 99%
“…Among these, flat spectrum radio quasars [38] are the most studied, but there are also significant contributions from star-forming galaxies, radio galaxies and Bl Lacertae objects. In the same figure, we plot the spectrum of star-forming galaxies for the case when the spectrum is determined from the IR luminosity function model (dashed line), and the integrated flux of flat spectrum radio quasars (dotted line) [38]. The predicted spectrum for star-forming galaxies strongly depends on the assumptions of the model and the magnitude accordingly varies by an order of magnitude.…”
Section: F Dark Matter Spike Mass Functionmentioning
confidence: 99%